STUDIES ON THE IMMUNOMODULATORY AND THERAPEUTIC EFFICACY OF NEEM (AZADIRACHTA IND/CA) ON ENDOMETRITIS IN REPEAT BREEDING CROSSBRED COWS - KUMAR, AMIT; GUPTA, H P; PRASAD, SHIV (The Indian Journal of Animal Reproduction, 2023)
An experiment was designed to investigate the immunomodulatory and therapeutic efficacy of neem onendometritis in repeat breeding crossbred cows. Twenty four cows were selected on the basis of history, breedingrecords, transrectal examination, white side test and randomly divided into 3 groups (Group A: 30 ml normalsaline; Group B: 30 ml hydro-alcoholic neem bark; Group C: 30 ml hydro-acetonic neem bark). Treatments weregiven intrauterine beginning on the day of estrus for seven days in each group. Cervical mucus samples werecollected on the day of estrus before treatment and at subsequent estrus after treatment and tested for appearance,pH, white side test and bacterial load. Blood samples were collected on the day of treatment and 24 hr aftertreatment and analyzed for glucose, Hb, PCV, TLC and DLC to know health status of the experimental animals.Uterine flushings were collected on the day of estrus before treatment and again on eighth day of first collectioni.e. 24 hr after last treatment. These flushings were used for the estimation of total protein, immunoglobulin, TLCand polymorphonuclear cells (PMNs). At subsequent standing estrus following treatment, all cows were artificiallyinseminated twice using frozen semen 12 hours apart. Pregnancy was confirmed transrectally 45-60 days afterinsemination. Significant (p
Keywords: Crossbred cows; Endometritis; Neem (Azadirachta indica); Repeat breeder